(untitled) (REMUNOM, 2023)
The Intensive Free-Range Pig System is characterized by keeping the animals in paddocks surrounded by wires, screens or wires and also containing stalls to hold them in some phases of breeding. It is also necessary to use vegetable matter, such as trees and grasses. SISCAL has become very widespread in several regions, because it is characterized by a free breeding system, allowing the animal to have contact with its natural habitat, leaving it free to graze, but also including a balanced diet of standard intensive. This technique has provided good results as it offers the animal comfort that it would be difficult to have just confined in stalls. Some producers have shown interest and opted to include this system as its implementation is more suited to the reality of small properties, as costs are more affordable using this breeding model. However, we must remember that it is of great importance to always value the health of the place by keeping the environment clean, offering quality water and food, it is extremely necessary to also include all prophylaxis measures, always paying attention to ethics and animal welfare. Therefore, poor adaptation of systems to correct management can affect development and productivity, interfering with the quality of the final product.